Shape-controlled synthesis of metal – organic frameworks with adjustable Fenton-like catalytic activity - Liu, Jiayi (2020)
Controllable synthesis of metal–organic frameworks with well-defined morphology, composition, and size is of great importance toward understanding their structure–property relationship in various applications. Herein, we demonstrate a general strategy to modulate the relative growth rate of the secondary building units (SBUs) along different crystal facets for the synthesis of Fe–Co, Mn0.5Fe0.5–Co, and Mn–Co Prussian blue analogues (PBAs) with tunable morphologies. The same growth rate of SBUs along the {100}, {110}, and {111} surfaces at 0 °C results in the formation of spherical PBA particles, while the lowest growth rate of SBUs along the {100} surface resulting from the highest surface energy with increasing reaction temperature induces the formation of PBA cubes. Fenton reaction was used as the model reaction to probe the structure–catalytic activity relation for the as-synthesized catalysts. The cubic Fe–Co PBA was found to exhibit the best catalytic performance with reaction rate constant 6 times higher than that of the spherical counterpart. Via density functional theory calculations, the abundant enclosed {100} facets in cubic Fe–Co PBA were identified to have the highest surface energy and favor high Fenton reaction activity.